De vita Mosis I: an introduction with text, translation, and notes - Philo, Alexandrinus 25 v.Chr.-40 (Ancient Christianity and its contexts, 2023)
This volume, a translation of book 1 of Philo of Alexandria’s De vita Mosis, with introduction and commentary, aims to introduce new readers, both students and scholars, to Philo of Alexandria through what is widely considered to be one of his most accessible works and one that Philo himself may have intended for readers unfamiliar with Judaism. The introduction provides historical, intellectual, and religious context for Philo, discusses major issues of scholarly interest, considers the relation of De vita Mosis to the Septuagint, and explores the immediate Nachleben of Philo’s works. The author’s translation is paired with Cohn’s edition of the Greek text, thereby providing not only a rendering of the Greek but also the Greek itself for those who wish to read Philo’s own words. The English rendering of the Greek aims at clarity and accuracy while retaining as many of Philo’s unique stylistic features as possible. Finally, the notes are designed to elucidate the text, especially for new readers, on a variety of levels: extrapolating on points more fully discussed elsewhere in the Philonic corpus, observing specific divergences from the Septuagint, and suggesting aspects of contemporary historical influence on Philo’s retelling of the biblical narrative. The volume serves as a succinct entry into the basics of Philo while also preparing the reader for some of Philo’s more challenging works